Depression and Coping Styles of College Students in China During COVID-19 Pandemic: A Systemic Review and Meta-Analysis - Guo, Shengyu; Kaminga, Atipatsa Chiwanda; Xiong, Jie (Frontiers in Public Health, 2021)
Abstract Background The rapid spread of COVID-19 around the world has seriously affected the life of college students. The impact of COVID-19 on college students' emotions has not been quantitatively assessed, and the application and communication characteristics of mental health mobile APPs among Chinese college students have not been quantitatively assessed. Objective To evaluate the impact of COVID-19 epidemic on the mood of college students, and the proportion of college students with different degrees of depression was obtained. The application status of mobile phone APPs and other new information communication platforms in college students during the COVID-19 epidemic was also assessed quantitatively. Methods A meta-analysis was conducted to quantitatively assess t impact of COVID-19 epidemic on the mood of college students, and five methods were used to evaluate whether the distribution of the main outcome (rate of depression) conforms the normal distribution. Results During the COVID-19 epidemic, the proportion of Chinese college students suffering from mild depression, moderate depression and severe depression was 25% ( 95CI:17%-33% ), 7% ( 95CI:2%-14% ) and 2% ( 95CI:1%-5% ), respectively. The proportion of college students who use WeChat and Weibo to acquire COVID-19 knowledge was 39%, and its 95% confidence interval was 13%-68%. Mental health APPs were often used by college students with depression, about 59% of depressed college students have used such APPs to deal with bad emotions (95% CI: 41%-73%). Conclusions The COVID-19 epidemic has led to higher rates of depression among college students, and university administrators should pay special attention to students suffering from moderate to severe depression and provide them with more professional mental health services. Social platforms (WeChat, Weibo, etc.) and social software ( including mobile APPs and public accounts) played an important role in spreading COVID-19 knowledge among college students. Mental health APPs were often used by college students with depression to cope with their bad emotion.